PEMBIAKAN BIBIT F2 JAMUR TIRAM (Pleurotus ostreatus) PADA BERBAGAI DOSIS DEDAK SECARA INVITRO MENGGUNAKAN MEDIA TANAM AMPAS SAGU - Sania dwintami; Adrianus Adrianus; Andri Prasetia; rosmala widijastuti (Musamus University, 2022)
Absract Sago palm waste is a potential media for oyster mushroom cultivation because of cellulose and lignin content,yet it still requires supplementary materials to improve the media,s nutritional status. This research aims to assess the effect of sago palm media supplemented with varying research was designed using a completely randomized design with one treatment factor consisting of four treatments (0g, 20g, and 30g) with 20 replications. The research result revealed that sago palm waste media supplementing with 30g of rice-milled waste is the best combination for mycelium growth in oyster mushrooms (Pleurotus ostreatus) F2 nursery. Keywords: Mushroom, Sago Palm Waste, Sago Palm Waste, Mycelium